Synthesis and antimicrobial activity of some new pyrazoline derivatives bearing sulfanilamido moiety - Almahdi, Maysoon Mohammed; Saeed, Ahmed Elsadig Mohammed; Metwally, Nadia Hanafy (European Journal of Chemistry, 2019)
In the present study, a series of new pyrazoline derivatives bearing sulfanilamido moiety were synthesized and obtained in good yields. The chemical structures of the compounds were elucidated by spectral data (FT-IR, MS, UV-VIS and NMR). The synthesized compounds 41-70 were screened for their antimicrobial activity and compared with controls. The in vitro antibacterial activity of compounds 41-45 and 48-57 was checked against two Gram positive microorganisms (S. aureus and S. mutans) and three Gram negative microorganisms (E. coli, K. pneumonia and P. aureginosa), their antifungal activity was checked against C. albicans. The preliminary results showed that these compounds had moderate activity against the tested organisms. Compounds 41, 48, 51 and 56 exhibited promising antimicrobial activity against S. aureus compared to standard drug Ampicilin. Final synthesized compounds 58-70 were tested against two Gram positive (S. aureus and B. subtilis) and two Gram negative (E. coli and P. aureginosa) microorganisms, their activity against C. albicans was also checked and they did not exhibit any antimicrobial activity.